Household Air Pollution and Respiratory Symptoms a Month Before and During the Stringent COVID-19 Lockdown Levels 5 and 4 in South Africa. Issue 1 (10th January 2022) - Wright, Caradee Y.; Kapwata, Thandi; Abdelatif, Nada; Batini, Chiara; Wernecke, Bianca; Kunene, Zamantimande; Millar, Danielle A.; Mathee, Angela; Street, Renée; Panchal, Rikesh; Hansell, Anna; Cordell, Rebecca; et al.
Background: Household air pollution (HAP) is associated with adverse human health impacts. During COVID-19 Lockdown Levels 5 and 4 (the most stringent levels), South Africans remained at home, potentially increasing their exposure to HAP. Objectives: To investigate changes in fuel use behaviours/patterns of use affecting HAP exposure and associated HAP-related respiratory health outcomes during COVID-19 Lockdown Levels 5 and 4. Methods: This was a cross-sectional online and telephonic survey of participants from an existing database. Logistic regression and McNemar's test were used to analyse household-level data. Results: Among 2 505 participants, while electricity was the main energy source for cooking and heating the month before and during Lockdown Levels 5 and 4, some households used less electricity during Lockdown Levels 5 and 4 or switched to "dirty fuels." One third of participants reported presence of environmental tobacco smoke in the home, a source of HAP associated with respiratory illnesses. Prevalence of HAP-related respiratory health outcomes were <10% (except dry cough). Majority of households reported cooking more, cleaning more and spending more time indoors during Lockdown Levels 5 and 4 – potentially exposed to HAP. Conclusion: Should South Africa return to Lockdown Levels 5 or 4, awareness raising about the risks associated with HAP as well as messaging information for prevention of exposure to HAP, including environmental tobacco smoke, and associated adverse health impacts will be necessary.